Factorial construct of the academic parental involvement according to paternity, maternity and study stage in Sultanate of Oman - Taghreed Turki Al Said; Ahmed Muhamed Shabib (Journal of Arts and Social Sciences, 2018)
The parental academic involvement is an important variable in achieving cooperation between home and school with the aim of improving the performance of their children and boosting the school's attempt to understand and appreciate the values and cultures of families to effectively meet the needs of their children. It is also considered an added value to develop the educational process of children at all ages. The importance of the research lies in its findings which reveal that the parental academic involvement of the selected sample of students in light of parenthood and school stage (secondary-university) is a decided advantage, as this makes a better understanding of this variable and its constituents in Oman. This would help draw guidelines and instructions and give rise to counseling programs, making parents and educationalists aware of the educational process, and improving the academic performance and the behavior of their different. The study sample consists of 210 students in their 10th grade at the secondary stage and 152 male and female students in their 2nd year in the College of Education at Sultan Qaboos University (SQU). Two scales were devised, one which is applied to secondary stage students and another applied to SQU students. The findings show that there are specific factors related to parental academic involvement concept, as there are fatherhood and motherhood factors applicable to secondary stage and others applicable to university students. These factors vary by type (Father-Mother) and the school stage (secondary–university).